HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL DALAM MEMENUHI KEBUTUHAN NUTRISI DENGAN STATUS GIZI DI PUSKESMAS SEMULA JADI KECAMATAN DATUK BANDAR TIMUR KOTA TANJUNGBALAI TAHUN 2020 - ROSTINA AFRIDA POHAN (JURNAL ILMIAH KOHESI, 2021)
Lack or excess food during pregnancy can result in less good for the fetus. Therefore, the input of nutrients in pregnantwomen will determine the health of the mother and fetus. The fetus is very dependent on his mother, from breathing, growthand to protect it from disease. The purpose of this study was to determine knowledge and attitude Relations pregnantmothers to meet the nutritional needs and nutrition status in Puskesmas Semula Jadi Tanjungbalai City 2020. This studyused a descriptive correlation research method with cross sectional design. The population in this study all pregnant womenwho visited the health center Semula Jadi Tanjungbalai as many as 33 people by using purposive sampling technique Dataanalysis was performed with chi-square test. The results showed that the photo there is a relationship of knowledge pregnantmothers to meet the nutritional needs and nutrition status in Puskesmas Semula Jadi 2020, this is evidenced by the resultsof chi-square test with p-value = 0,000 and there is a relationship between pregnant mothers to meet needs nutrition withnutritional status in Puskesmas Semula Jadi Tanjungbalai 2020 with the results of chi-square test with p-value = 0.046.Suggestion For pregnant women are expected to be more routine checkups for health workers and actively participating incounseling conducted by health officials to obtain information relating to nutrition during pregnancy.